The Compulsory Act in Jumanji (2017) Movie: Demonstration of Gender Performativity Fluidity - Sharenlie, Grania; Djohan, Febrina Stevani; Purnama, Aurellia Zureil; Sihotang, Chrishanna Rose; Riven, Abednego Rick; Jesua, Uniqua Abigail (Jurnal Pendidikan Makarios, 2026)
This research analyzes the film Jumanji: Welcome to the Jungle (2017) to understand that gender is a repeated action rather than a fixed biological identity, using Judith Butler's theory of Gender Performativity (1990). By using a qualitative method to focus on the narratives and dialogues, this study examines through the body-swaps of character between the four main characters, also the challenges that the characters face on the new avatar’s body. The findings show: 1) Bethany's transformation serves as a deconstruction gender as a biological and fixed identity; 2) Martha's struggle with her role that demonstrates gender is a set of compulsory, subversive repetition; and 3) The character's adaptation reveals that identity is fluid and created by personal choice, not rigid social rules. This study concludes that the film serves as a powerful illustration for gender fluidity. This research is significant as it highlights that a fun, and popular movie may help people understand complex ideas about identity and gender while encouraging audiences to think critically about the stereotypes in everyday life. It is hoped that future researchers will apply similar critical lenses to other narratives to further explore how media influences the fluid construction of gender identity.